A review and call for domestication of the United Nations convention on the rights of persons with disabilities in Nigeria (2016)
The Convention on the Rights of Persons with Disabilities (CRPD) has been rated the most widely subscribed United Nations (UN) instrument within a short time after it was adopted in 2006. As at October 2012, the CRPD had been ratified by 125 countries including Nigeria. The high level of acceptance and eagerness of many countries to adopt the CRPD shows that the CRPD was a something the global community had been waiting for. It is also indicative that there had been a wide spread shift in the paradigm of understanding of the concept of disability as well as the human right status of persons with disabilities (PWDs). The high level of participation in negotiating the CRPD marked a definite break from previous approaches that did not pay attention to the rights of PWDs. The article adopted the content analysis research method. It started with a theoretical background and then x-rayed the text of the CRPD, bringing to the fore, unique provisions, including 'reasonable accommodation’ which meets the specific needs that may arise from disability and which may need to be met before some PWDs can fully exercise their rights. Universal Design, which is both needful and economical, is also a unique concept in the CRPD (such as the provision of a ramp instead of a stair case). It concludes that Nigeria's domestication of the CRPD is both for its benefit and an obligation under section 12 of the 1999 Constitution of the Federal Republic of Nigeria (as amended).